On the Egyptian origin of Judith, or Judith as Anath-Yahu - Efthimiadis-Keith, Helen (Journal for semitics, 2011)
This article puts forward a possible Egyptian origin for the book of Judith (Judith). The hypothesis is based on three inter-linking factors: the Samaritan links in the book; Judith's dual nature, which strongly resembles that of Anat; and the events in Judith which find strong parallels in the history of the Egyptian Jews at Elephantine and Leontopolis. In order to reach its goal, the article merges certain historical-critical methods with the author's favoured Jungian psychoanalytic approach.